2012
DOI: 10.1002/jbmr.1754
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen receptor-α is required for the osteogenic response to mechanical loading in a ligand-independent manner involving its activation function 1 but not 2

Abstract: Estrogen receptor-α (ERα) is crucial for the adaptive response of bone to loading but the role of endogenous estradiol (E2) for this response is unclear. To determine in vivo the ligand dependency and relative roles of different ERα domains for the osteogenic response to mechanical loading, gene-targeted mouse models with (1) a complete ERα inactivation (ERα−/−), (2) specific inactivation of activation function 1 (AF-1) in ERα (ERαAF-10), or (3) specific inactivation of ERαAF-2 (ERαAF-20) were subjected to axi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
101
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 90 publications
(114 citation statements)
references
References 57 publications
12
101
1
Order By: Relevance
“…[35][36][37] In a subsequent study, incomplete deletion of ERb was found to reduce the osteogenic response in the ulna of female mice similarly to ERa deletion, 37 suggesting that the two ERs complemented each other's function in the mechanostat. However, studies using more complete ERb knockout mice suggest an enhanced response to loading in the cortical bone of both male and female mice 36 (Figure 2).…”
Section: Era Promotes Cortical Bone Mass Through Its Action In Early mentioning
confidence: 89%
See 1 more Smart Citation
“…[35][36][37] In a subsequent study, incomplete deletion of ERb was found to reduce the osteogenic response in the ulna of female mice similarly to ERa deletion, 37 suggesting that the two ERs complemented each other's function in the mechanostat. However, studies using more complete ERb knockout mice suggest an enhanced response to loading in the cortical bone of both male and female mice 36 (Figure 2).…”
Section: Era Promotes Cortical Bone Mass Through Its Action In Early mentioning
confidence: 89%
“…Windahl et al 35 investigated this by ovariectomizing mice before subjecting their tibiae to loading. Ovariectomy did not alter the loading-related increase in bone formation at either the periosteal or endosteal surface, whereas global deletion of ERa significantly reduced the increase in formation on both surfaces.…”
Section: Era Promotes Cortical Bone Mass Through Its Action In Early mentioning
confidence: 99%
“…Previous studies have demonstrated that female but not male mice with ERα inactivation display reduced cortical osteogenic bone response to mechanical loading (19,(21)(22)(23)(24). In addition, we recently showed that ERα is required for the cortical osteogenic response to mechanical loading in a ligand-independent manner, involving activation function-1 but not activation function-2 in ERα in female mice (20). The primary ERα target cell for this role of ERα in the osteogenic bone response to mechanical loading is not yet characterized, but a plausible candidate is the osteocytes, which are the mechanosensors in bone.…”
mentioning
confidence: 85%
“…It is well established that mechanical loading is a major regulator of cortical bone dimensions (19,20). Previous studies have demonstrated that female but not male mice with ERα inactivation display reduced cortical osteogenic bone response to mechanical loading (19,(21)(22)(23)(24).…”
mentioning
confidence: 99%
“…In vivo tibia loading. The protocol for noninvasively loading the mouse tibia has been reported previously (1,26,37,41). Briefly, while under inhalation anesthesia with Isoflurane (Forene; Abbot Scandinavia, Solna, Sweden), the right tibia of mice aged 6 (control, n ϭ 11; LI-IGF-I Ϫ/Ϫ , n ϭ 9) or 19 mo (control, n ϭ 8; LI-IGF-I Ϫ/Ϫ , n ϭ 7) was axially loaded on 3 alternate days/wk for 2 wk (days 1, 3,5,8,10, and 12) for 40 cycles/day with a trapezoid waveform, with 10 s of rest between cycles.…”
Section: Animals and Serum Igf-i The Li-igf-imentioning
confidence: 99%